Motilitas dan Viabilitas Spermatozoa Babi dalam Pengencer Air Kelapa-Kuning Telur Ayam Kampung - Crecentia Aprilinda Butta; Cynthia Dewi Gaina; Nancy D F K Foeh (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2021)
The aims of this study is to determine the effect and the best combination of coconut water (CW) and native chicken egg yolk (NCEY) as extender with water jacket and non-water jacket method in preserving of boar semen. Semen was collected from sexualy mature boar 2-4 years of age. A good sample of semen will have motility above 70%, abnormality below 20% and spermatozoa consentration above 200 x 106 sel/mL. This study was designed with completly randomized design and faktorial patern with 2 controled group, 6 treated group, and 4 repitition. Controled group consist of fresh semen without extender. K0 was preserved with non-water jacket method, and K1 was preserved with water jacket method. Treated group were P1 (75% CW + 25% NCEY), P2 (85% CW + 15% NCEY), P3 (95% CW + 5% NCEY) that preserved with non-water jacket method, and P4 (75% CW + 25% NCEY), P5 (85% CW + 15% NCEY), P6 (95% CW + 5% NCEY) preserved with water jacket method. Motility and viability of spermatozoa were evaluated every 2 hours until motility value has reached 40%. The result shows that P3 and P5 is the best combination for preserving semen (32 hours). Water jacket method is the better option for preserving boar semen. P3 is the least in preserving boar semen.